2022
DOI: 10.1525/fsr.2022.34.2-3.119
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Practice of Utilizing Bonds to Cover Legal Financial Obligations

Abstract: Cash bail payments are generally imposed to ensure an individual appears in court after arrest. Lesser known is the practice of bond conversion, wherein bond money is held to pay for legal financial obligations if the individual is found guilty. Procedural justice theory is a useful framework for understanding bail processes. Individuals subject to bond conversion may experience distrust towards a system whose policies are not transparent, potentially reducing compliance with the law. We conduct an assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… For a discussion of the process and legal context of bond conversion (i.e., the use of bail bonds to pay for LFOs), see Diaz et al. (2022). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… For a discussion of the process and legal context of bond conversion (i.e., the use of bail bonds to pay for LFOs), see Diaz et al. (2022). …”
mentioning
confidence: 99%
“…"8 In many states, offenders pay both restitution and compensation, the latter of which is assessed to all offenders, regardless of if there was a direct victim in that situation; see also,Katzenstein and Waller (2015) andMartin and Fowle (2020).9 Two recent works discuss this in greater depth:Harris et al (2019) provide two case studies that demonstrate how private entities, which run court-ordered programs and prison services, profit from LFOs;Katzenstein et al (2020) discuss "commissions/kickbacks" which funnel fees to private entities when incarcerated people, their families, or their friends pay for the use of a prison phone, commissary, or other services.10 SeeNeedham et al (2020) for an ethnographic account of the confusion faced by those assessed legal debt in fine-only misdemeanor cases.11 See alsoLink's review (2022) which presents some conflicting evidence on the relationship between LFO debt and increased recidivism rates, including a list of studies that found null effects or inverse relationships. The author then conducts an analysis of prison reentry data from three cities and finds null effects, concluding that more research is needed to disentangle the precise impact of LFOs on recidivism.12 For a discussion of the process and legal context of bond conversion (i.e., the use of bail bonds to pay for LFOs), seeDiaz et al (2022).13While Bearden v. Georgia (1983) found that the court could not sentence a person to jail or prison for nonpayment of LFOs unless it held a hearing to determine that the person "willfully" did not pay, many jurisdictions, in practice, do not hold those hearings or interpret the idea of "willful nonpayment" through moralized and racialized ways that further penalize the individuals.…”
mentioning
confidence: 99%